Constructor de Fracciones - Agüero-Calvo, Evelyn (My University, 2021)
En este video se les presenta una aplicación interactiva elaborada por la Universidad de Colorado, gratuita y de uso libre, que se ejecuta directamente en el navegador. También se puede descargar y enviar el archivo. Enlace: https://phet.colorado.edu/sims/html/fractions-intro/latest/fractions-intro_es.html

This video introduces you to a free, open-source, interactive application developed by the University of Colorado that runs directly in your browser. You can also download and send the file. Link: https://phet.colorado.edu/sims/html/fractions-intro/latest/fractions-intro_en.html
Keywords: Fracciones; Aplicación interactiva; Representaciones graficas; Aritmética; Matemáticas; Fractions; Interactive application; Graphic representations; Arithmetic; Mathematics